The use of platelet rich plasma in the treatment of degenerative joint disease in cats: an exploratory case series - Huntingford, Janice; Looney, Andrea; Johnson, James; Miller, Lisa (Frontiers in Veterinary Science, 2024)
Objective To evaluate the effectiveness of intra-articular autologous Platelet Rich Plasma (PRP) in managing Degenerative Joint Disease (DJD) in cats. Design Prospective pilot clinical trial. Methods Six domestic cats with clinically and radiographically diagnosed DJD received intra-articular injections of autologous PRP. Clinical assessments pre and post intra-articular injections were conducted using the Feline Musculoskeletal Pain Index (FMPI, owner assessed) and Visual Analog Scale (VAS, clinician assessed) at baseline, Day 14, Day 28, and Day 42–45. Results Significant improvements were noted in both FMPI and VAS scores at the end of the study period, indicating enhanced joint function and reduced pain. Conclusion and clinical relevance The study suggests the potential of PRP therapy as a safe and effective treatment for feline DJD, warranting further research with larger cohorts and longer follow-up to establish comprehensive treatment guidelines.